Existence of a pure-strategy Bayesian Nash equilibrium in imperfectly discriminating contests - Cédric Wasser (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We consider a general class of imperfectly discriminating contests with privately informed players. We show that findings by Athey (2001) imply the existence of a Bayesian Nash equilibrium in monotone pure strategies.
urn:nbn:de:bvb:19-epub-13223-8
Keywords: D72; D74; D82; C72; 330; contest; imperfectly discriminating; asymmetric information; equilibrium existence; interdependent values; Wettbewerb; Nichtkooperatives Spiel; Asymmetrische Information; Nash-Gleichgewicht; Theorie